Cellulose extraction from corn husk and its modification with metal-organic framework and its use to remove pharmaceutical pollutants - Alireza Hazrati; mehdi barzegarzadeh; Mohammad Sadegh Aminifazl (علوم و تکنولوژی پلیمر)
Hypothesis: Today, the widespread use of drugs in health care has led to their significant flow into aquatic environments, which has negative effects on the health of the environment. One of the methods used to remove drugs from water is the chemical adsorption method, which is suggested as an efficient method for removing drugs from water due to its simple operation and cost-effectiveness.Methods: In this study, cellulose was extracted from corn husk and then it was magnetized using iron oxide nanoparticles by coprecipitation method and in order to increase the specific surface area and adsorption efficiency, it was modified with aluminum metal-organic framework (Cellulose@Fe3O4/Al-MOF). Magnetic cellulose adsorbent modified with metal-organic framework was used as a biosorbent to remove the drug doxorubicin from aqueous media. The chemical structure, crystallinity, morphology, particle size and other properties of the absorbent were investigated and confirmed using SEM, XRD, FT-IR and VSM analyses.Findings: The parameters affecting the maximum absorption of doxorubicin including pH, initial concentration, adsorbent amount and contact time were optimized using Taguchi's statistical method and in optimal conditions of pH = 6, the initial concentration was equal to 20 ppm, the amount of adsorbent was equal to 2 g/L, and in 80 minutes, the absorption capacity was 88%. The isotherm follows the Langmuir model, and the kinetics corresponds to the pseudo-first-order model, and the maximum absorption capacity was predicted as 96.15 mg/g according to the Langmuir model. In addition, the thermodynamic study showed that the adsorption process of doxorubicin drug by magnetic cellulose modified with metal-organic framework adsorbent is spontaneous, exothermic and associated with entropy reduction. Also, the results of the adsorption-desorption study showed that the adsorbent has very good stability; Because it can be reused for 7 cycles without losing its effectiveness.